Analysing foreign market entry: the choice between greenfield investment and acquisitions - Holger Görg (Trinity College, Department of Economics, 1998)
This paper formalises the choice a firm has to face when entering a foreign market via FDI as between setting up an entirely new plant (greenfield investment) or acquiring an existing indigenous firm. Our results show that in an asymmetric duopoly situation a new entrant will normally be best off by acquiring an existing indigenous low-technology firm, thus, forming a duopoly with an indigenous high-technology firm. While in welfare terms the entry of the foreign firm damages the country in most cases, there exist some possibilities that welfare, particularly after a greenfield investment by the foreign firm, is higher than before entry, even when there is full profit repatriation.
Keywords: F23; L13; 330; Markteintritt; Direktinvestition; Duopol; Wohlfahrtseffekt; Theorie